Hersz Wasser. Sekretarz Archiwum - Person, Katarzyna (Zagłada Żydów. Studia i Materiały, 2014)
This article discusses the life of Hersch Wasser (1910–1980), secretary of the “Oneg Shabbat” and the closest collaborator of Emmanuel Ringelblum. Wasser, an economist from Łódź, who was a key personality in the Underground Archive of the Warsaw Ghetto. He was the one who coordinated its activities and recorded both its collaborators and incoming documents. He was one of the creators of the press department of the “Oneg Shabbat”, which provided information on the Holocaust to the Polish and Jewish underground press. As a secretary of the Central Refugee Commission, he interviewed refugees arriving in the ghetto and supplied the Archive with information on the persecution of Jews outside Warsaw. After the end of the war, Wasser played a key role in unearthing the first part of the Underground Archive in September 1946 and in preparing their first catalogue. Simultaneously, between April and September 1947, Wasser took out about 140 documents from the collection and together with other documents relating to the Holocaust (altogether 244) sent them to YIVO in New York, seeing it as a way of safekeeping them in the face of a dif????icult situation in post-war Poland. He emigrated to Israel in 1950.